Contribuição para a normalização da alvenaria estrutural com uso de tijolos de terra crua para construções urbanas - Gonçalves, Jameson da Silva (2005)
The production of industrialized materials, like concrete, ceramic bricks and steel, consumes enormous amounts of energy, throws pollutants in the atmosphere and generates absurd amounts of harmful residues into the environment. In spite of this, they have been strongly studied in all the engineering and architecture schools in the whole world. With already almost seven billion people, which almost half has an enormous need of infrastructure and housing, but at least half hasn t income to acquire the industrialized materials, another solution doesn't have the Earth Planet, than to return to the past and seek in the planet how to survive without attacking it intensely. In the Engineering field, if one hypothetically wants to supply the needs of the emerging countries only with the industrialized materials, considering that a single kilogram of cement consumes more than 2.6 kWh, there would probably be the energy collapse in the globe! So, the search for natural materials becomes an option for the future. In the area of the construction, among the beneficial materials to the human beings there are the raw earth that accompanies them from the humanity's origins. As it is still little studied, the raw earth is banished practically as construction material, despite all its history. This work presents a series of studies done in layers of raw earth, constructed using two technologies: the one of the pressed bricks and the one of the adobes. Eleven walls were tested, six of them in blocks pressed as Mattone type, that is, a brick with fittings that uses a flowing mortar with a small thickness in the assembly of the walls. The loads were applied in cycles, to verify the behavior of the walls also in unloading. On the top of the walls a beam of armed concrete was built to distribute the applied load applied by hydraulic jacks. The behavior of the walls was accompanied through measurements done by mechanical extensometer with which they were instrumented. The results showed a surprising capacity of carrying load of the wall panels, that, although there were load eccentricities always present in the tests, they behaves in a way more than satisfactory for use in community equipments and houses of social interest